Management, Functional Outcomes, and Quality of Life After Development of Pelvic Sepsis in Patients Undergoing Re-Do Ileal Pouch Anal Anastomosis. Issue 8 (5th July 2022) - Esen, Eren; Grieco, Michael J.; Erkan, Arman; Aytac, Erman; Sutter, Alton G.; Lynn, Patricio Bernardo; Esterow, Joanna; da Luz Moreira, Andre; Kirat, Hasan T.; Remzi, Feza H.
Abstract : BACKGROUND: The data on management and outcomes of pelvic sepsis after re-do IPAA are scarce. OBJECTIVE: The aim of this study is to report our management algorithm of pelvic sepsis in the setting of re-do IPAA and compare functional outcomes and quality of life after successful management of pelvic sepsis with a no sepsis control group. DESIGN: This is a retrospective cohort study. SETTINGS: This investigation is based on a single academic practice group experience on re-do IPAA. PATIENTS: Patients who underwent re-do IPAA for ileal pouch failure between September 2016 and September 2020 were included in the study. MAIN OUTCOME MEASURES : Management of pelvic sepsis was reported. Functional outcomes, restrictions, and quality-of-life scores were compared between the sepsis and no sepsis groups. RESULTS: One-hundred ten patients were included in our study, of whom 25 (22.7%) developed pelvic sepsis. Twenty-three patients presented with pelvic sepsis before ileostomy closure, and 2 patients presented with pelvic sepsis after ileostomy closure. There were 6 pouch failures in the study period due to pelvic sepsis. Our management was successful in 79% of the patients with median follow-up of 26 months. Treatments included interventional radiology abscess drainage (n = 7), IV antibiotics alone (n = 5), interventional radiology drainage and mushroom catheter placement (n = 1), mushroom catheter placement (n = 1), and endoluminal vacuum-assisted closure (n = 1). Average number of bowel movements, urgency, incontinence, pad use, and seepage were comparable between the pelvic sepsis and no pelvic sepsis groups ( p > 0.05). Lifestyle alterations, Cleveland Global Quality of Life scores, and happiness with the results of the surgery were similar ( p > 0.05). LIMITATIONS: This study is limited by its low study power and limited follow-up time. CONCLUSIONS: Pelvic sepsis is common after re-do IPAA, and management varies according to the location and size of the abscess/sinus. If detected early, our management strategy was associated with high pouch salvage rates. See Video Abstract at http://links.lww.com/DCR/B823 . MANEJO, RESULTADOS FUNCIONALES Y CALIDAD DE VIDA DESPUÉS DEL DESARROLLO DE SEPSIS PÉLVICA EN PACIENTES SOMETIDAS A RECONFECCIÓN DE ANASTOMOSIS ANAL CON BOLSA ILEAL: ANTECEDENTES: Los datos sobre el tratamiento y los resultados de la sepsis pélvica después de reconfección de anastomosis anal, de la bolsa ileal son escasos. OBJETIVO: El objetivo de este estudio es informar nuestro algoritmo de manejo de la sepsis pélvica en el contexto de reconfección de anastomosis anal de la bolsa ileal y comparar los resultados funcionales y la calidad de vida después del manejo exitoso de la sepsis pélvica con un grupo de control sin sepsis. DISEÑO: Este es un estudio de cohorte retrospectivo. AJUSTES: Esta investigación se basa en una experiencia de un solo grupo de práctica académica sobre reconfección de IPAA. PACIENTES: Se incluyeron en el estudio pacientes que se sometieron a una nueva anastomosis anal, del reservorio ileal por falla del reservorio ileal entre el 09/2016 y el 09/2020. PRINCIPALES MEDIDAS DE RESULTADO: Se informó el manejo de la sepsis pélvica. Los resultados funcionales, las restricciones y las puntuaciones de calidad de vida, se compararon entre los grupos con sepsis y sin sepsis. RESULTADOS: Se incluyeron 110 pacientes en nuestro estudio, de los cuales 25 (22, 7) desarrollaron sepsis pélvica. Veintitrés pacientes presentaron sepsis pélvica antes del cierre de la ileostomía y 2 pacientes presentaron sepsis pélvica después del cierre de la ileostomía. Hubo 6 fallas de la bolsa en el período de estudio debido a sepsis pélvica. Nuestro manejo fue exitoso en el 79% de los pacientes con una mediana de seguimiento de 26 meses. Los tratamientos incluyeron drenaje de abscesos IR (n = 7), antibióticos intravenosos solos (n = 5), drenaje IR y colocación de catéter en forma de hongo (n = 1), colocación de catéter en forma de hongo (n = 1) y cierre endoluminal asistido por vacío (n = 1). El número promedio de evacuaciones intestinales, urgencia, incontinencia, uso de almohadillas y filtraciones fueron comparables entre los grupos con sepsis pélvica y sin sepsis pélvica ( p > 0, 05). Las alteraciones del estilo de vida, las puntuaciones de la Calidad de vida global de Cleveland y la felicidad con los resultados de la cirugía fueron similares ( p > 0, 05). LIMITACIONES: Este estudio está limitado por su bajo poder de estudio y su tiempo de seguimiento limitado. CONCLUSIONES: La sepsis pélvica es común después de la reconfección de anastomosis anal de la bolsa ileal y el manejo varía según la ubicación y el tamaño del absceso / seno. Si se detecta temprano, nuestra estrategia de manejo se asoció con altas tasas de recuperación de la bolsa. Consulte Video Resumen en http://links.lww.com/DCR/B823 . (Traducción—Dr. Mauricio Santamaria )